Analysis of Curriculum Component Integration in Vocational High Schools and its Relevance to Industry Standards - Fadhillah, Lola; Susilana, Rudi; Dewi, Laksmi (Jurnal Teknologi Pendidikan : Jurnal Penelitian dan Pengembangan Pembelajaran, 2025)
This study aims to analyze the integration of curriculum components that include objectives, content, learning strategies, and evaluation in the context of vocational education in Vocational High Schools (SMK), and examine their relevance to industry standards. This research used a descriptive qualitative approach with a collective case study method at three private vocational schools in Medan. Data were obtained through in-depth interviews, participatory observation, and documentation, then analyzed interactively based on the Miles and Huberman model. The results showed that there are integrative efforts from each school, but they are not yet fully aligned with industry needs. The main obstacles lie in the lack of ongoing collaboration with industry as well as limitations in adopting technology and evidence-based curriculum updates. This research emphasizes the importance of synergy between educational institutions, government, and the industry sector in designing and implementing a vocational curriculum that is contextual and responsive to changes in technology and the job market.